The use of CBT-oriented group guidance as a preventive intervention against bullying among adolescents - Yuliana Yuliana; Puji Gusri Handayani; Nurul Fajri; Susiati Susiati; Wa Ode Lili Andriani Nasri; Olfakhrina Olfakhrina (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Bullying among adolescents remains a persistent problem that negatively affects students’ psychological, social, and academic well-being. Although Cognitive Behavioral Therapy (CBT) has frequently been used to address bullying-related problems, its application within group guidance as a preventive intervention remains limited. Therefore, this study aimed to examine the potential effectiveness of CBT-oriented group guidance in reducing bullying behavior tendencies among adolescents. This study employed a quantitative approach using a pre-experimental one-group pretest–posttest design. The participants consisted of 10 students from SMK Maitreyawira Batam who demonstrated moderate to high bullying behavior tendencies. The intervention was implemented through structured group guidance sessions incorporating psychoeducation, cognitive restructuring, behavioral exercises, and emotional regulation training. Data were collected using a modified bullying behavior questionnaire and analyzed using the Wilcoxon Signed Rank Test. The results showed a significant reduction in bullying behavior tendency scores following the intervention (p = 0.003). Descriptive analysis indicated that all participants shifted from the high category to the moderate category. These findings suggest that CBT-oriented group guidance may contribute to reducing bullying behavior tendencies among adolescents. However, the findings should be interpreted cautiously due to the small sample size and the absence of a control group.